2020
DOI: 10.3390/nano10112309
|View full text |Cite
|
Sign up to set email alerts
|

Barium Titanate (BaTiO3) Nanoparticles Exert Cytotoxicity through Oxidative Stress in Human Lung Carcinoma (A549) Cells

Abstract: Barium titanate (BaTiO3) nanoparticles (BT NPs) have shown exceptional characteristics such as high dielectric constant and suitable ferro-, piezo-, and pyro-electric properties. Thus, BT NPs have shown potential to be applied in various fields including electro-optical devices and biomedicine. However, very limited knowledge is available on the interaction of BT NPs with human cells. This work was planned to study the interaction of BT NPs with human lung carcinoma (A549) cells. Results showed that BT NPs dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…[117,269] In a study, a concentration range of 25-100 µg mL −1 of BaTiO 3 NPs was highlighted to shown decrease in cell viability in case of human lung cancer cells (A549) with a dose rate of 50 µg mL −1 of BaTiO 3 NPs showing pronounced oxidative stress. [117] Similar results were also presented in a separate study by Staedler et al where a time dependent cytotoxicity of BaTiO 3 NPs (50 µg mL −1 ) was evaluated on A549 cells with % cell survival of almost 91%, 84%, and 81% after an exposure of 24, 48, and 74 h, respectively. [270] The cell survival rate and the dose to be administered is much dependent on the category of cell lines and the exposure time.…”
Section: Toxicity Assessment and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…[117,269] In a study, a concentration range of 25-100 µg mL −1 of BaTiO 3 NPs was highlighted to shown decrease in cell viability in case of human lung cancer cells (A549) with a dose rate of 50 µg mL −1 of BaTiO 3 NPs showing pronounced oxidative stress. [117] Similar results were also presented in a separate study by Staedler et al where a time dependent cytotoxicity of BaTiO 3 NPs (50 µg mL −1 ) was evaluated on A549 cells with % cell survival of almost 91%, 84%, and 81% after an exposure of 24, 48, and 74 h, respectively. [270] The cell survival rate and the dose to be administered is much dependent on the category of cell lines and the exposure time.…”
Section: Toxicity Assessment and Limitationsmentioning
confidence: 99%
“…BaTiO 3 NPs are susceptible to produce oxidative stress in the cancerous cells as reported by Ahamed et al by studying the interaction of BaTiO 3 NPs with human lung carcinoma (A549) cells. [ 117 ] The study reported the oxidative stress mediated, dose, and time dependent cytotoxicity upon interaction of the cells with BaTiO 3 NPs together with diminution of mitochondrial membrane potential and stimulation of related enzymatic activity (caspase‐3/‐9). Here, the oxidative stress was induced due to production of pro‐oxidants (ROS and H 2 O 2 ) and decline of antioxidants (glutathione).…”
Section: Batio3 Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…BaTiO 3 has been used in electromechanical actuators and in photo-galvanic devices, moreover, as a ceramic material is used in capacitors and sensors while the optical properties of the single crystal also present a great interest for non-linear optics applications [6][7][8]. Also has been reported the potential of the BaTiO 3 nanoparticles to be applied in biomedical elds, including tissue engineering, drug delivery, and cancer therapy [9][10][11][12][13]. On the other hand, BaTiO 3 has been applied as a catalyst for photocatalytic or piezocatalytic degradation of organic and inorganic pollutants in water with some modi cations to tune their properties for that purpose.…”
Section: Introductionmentioning
confidence: 99%
“…ROS regulate several cellular processes, such as proliferation, migration, and differentiation, at the physiological level [ 8 ]. However, an increase in ROS may cause cytotoxicity and is associated with conditions such as cancer, neurodegeneration, aging, and calcification of blood vessels [ 9 , 10 , 11 , 12 ]. Recent studies have shown that ROS can promote osteoporosis progression by inducing osteoblast death [ 13 ].…”
Section: Introductionmentioning
confidence: 99%